The benzoyl-CoA pathway serves as a genomic marker to identify the oxygen requirements in the degradation of aromatic hydrocarbons - Godínez-Pérez, Camila Monserrat; Loza, Antonio; Hurtado, Juan Manuel; Gutiérrez-Ríos, Rosa-María (Frontiers in Microbiology, 2024)
The first step of anaerobic benzoate degradation is the formation of benzoyl-coenzyme A by benzoatecoenzyme A ligase (BCL). The anaerobic route is steered by benzoyl-CoA reductase, which promotes the breakdown of benzoyl-CoA, which is subsequently oxidized. In certain bacteria at low oxygen conditions, the aerobic metabolism of monoaromatic hydrocarbons occurs through the degradation Box pathway. These pathways have undergone experimental scrutiny in Alphaproteobacteria and Betaproteobacteria and have also been explored bioinformatically in representative Betaproteobacteria. However, there is a gap in our knowledge regarding the distribution of the benzoyl-CoA pathway and the evolutionary forces propelling its adaptation beyond that of representative bacteria. Therefore, in this study, we used a set of bioinformatic procedures for identifying BCLs and the lower pathways that transform benzoyl-CoA, with the aim of answering these questions; moreover, we propose a set of genomic markers useful for identifying oxygen requirements in the degradation of benzoate and related monoaromatic hydrocarbons. These procedures included the identification of conserved motifs, two of which were exclusive to the BCLs, describing catalytic properties of this enzyme. Our approach effectively discerned BCLs from other aryl-CoA ligases. The predicted BCLs and the enzymes of lower pathways were used as genomic markers for identifying aerobic, anaerobic, or hybrid catabolism in the species analyzed, observing it widely preserved in Betaproteobacteria. Despite these enhancements, our approach failed to distinguish orthologs from a small cluster of paralogs that exhibited all the specified features to predict an ortholog. Nonetheless, the conducted phylogenetic analysis and the properties identified in the genomic context aided in formulating hypotheses about how this redundancy contributes to refining the catabolic strategy employed by these bacteria to degrade the substrates.